Prosperity prospects in contested forest areas: evidence from community forestry development in Guatemala and Nicaragua - Stoian, D.; Rodas, A.; Arguello, J. (2016)
Tropentag, September 18-21, 2016, Vienna, Austria “Solidarity in a competing world — fair use of resources” Prosperity Prospects in Contested Forest Areas: Evidence from Community Forestry Development in Guatemala and Nicaragua Dietmar Stoian 1 , Aldo Rodas 2 , Jessenia Arguello 3 1 Bioversity International, Healthy Diets from Sustainable Food Systems Initiative, France 2 Ministry of Agriculture and Livestock, Guatemala, Natural Resources and Agrotourism, 3 Independent Consultant, Abstract Community forestry is carried out under diverse institutional, environmental, and socio-economic conditions. Local communities may have de jure rights to forest resources, but de facto protection is often weak. This study focuses on 25-year community concessions in the Maya Biosphere Reserve (MBR) in Guatemala and indigenous territories in the North Caribbean Coast Autonomous Region (RACCN), Nicaragua. In both cases, communities are struggling to enforce their rights as powerful external groups seek to expand cattle ranching, cash crops, tourism, and oil exploration. We found evidence that community forestry can generate significant socio-economic benefits that, along with contributions to forest conservation, substantiate the communities’ claim for strengthened and extended community forest stewardship. We selected six community forest enterprises (CFEs) along a business development gradient and assessed their context, economic viability, and livelihood benefits among randomly selected CFE members (n=180). Adopting an asset lens, we determined human, social, natural, physical and financial capital endowments at household and enterprise levels. Enterprise assets varied widely, both within and across countries. CFEs were well endowed with natural capital (7,000–54,000 ha of broadleaf forests) but highly dependent on precious woods, such as mahogany ( Swietenia macropylla ) or andiroba ( Carapa guianensis ). Human capital was sufficiently developed for managing forests, but less so for processing wood and doing business. Social capital has been built in Guatemala through internal organisation, bringing CFEs under the umbrella of a regional association, and developing relationships with buyers. In Nicaragua, however, building of social capital has been insufficient for inducing a self-sustaining process of CFE development. Physical capital for logging and wood processing was moderate but, in Guatemala, conditions facilitate significant value adding. CFEs there were profitable, while those in the RACCN struggled to break even. Household assets varied widely but, in the MBR, we found evidence that forest-based income can lift people out of poverty. Our analyses reveal that critical success factors for community forestry to reduce poverty, conserve forests and enhance equity are: secure long-term forest usufruct rights or ownership, efficient business organisation, credible advocacy, a conducive service environment, and differentiated opportunities for women, men and youth.